2016
DOI: 10.1007/s13187-016-1087-1
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities and Barriers to the Use of Supportive Care Among Young Breast Cancer Survivors: a Qualitative Understanding

Abstract: The development of supportive care for cancer patients has been shown to have a positive impact on both mortality rates and many aspects of life after cancer, particularly in young women. Meanwhile, there are still numerous inequalities in terms of cancer mortalities and quality of life among cancer survivors in France. The processes leading to unequal access to supportive care services, and the impact this has on the post-treatment period, have been poorly documented, however. The goal of this study was to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The limited use of inpatients and especially personalized intensive outpatient's rehabilitation plans observed in our retrospective analysis suggest the lack of rehabilitative offer and the existence of barriers to patients' access. Although only few studies have speci cally evaluated the barriers to rehabilitation in women with BC [19,20], literature data in the cancer population suggest that lack of awareness and lack of physician referral are the main causes that restrict the use of rehabilitation services [33]. In the case of BC, we also believe that interventions [19,20].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The limited use of inpatients and especially personalized intensive outpatient's rehabilitation plans observed in our retrospective analysis suggest the lack of rehabilitative offer and the existence of barriers to patients' access. Although only few studies have speci cally evaluated the barriers to rehabilitation in women with BC [19,20], literature data in the cancer population suggest that lack of awareness and lack of physician referral are the main causes that restrict the use of rehabilitation services [33]. In the case of BC, we also believe that interventions [19,20].…”
Section: Discussionmentioning
confidence: 96%
“…Increasing the level of information and understanding of oncological rehabilitative services is an important step to overcome the existing barriers and to promote a more equal and comprehensive access of rehabilitation interventions in women with BC [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Social support is a key point to explain inequalities in waiting times between the first imaging procedure and the first treatment ( 77 ). There is qualitative evidence that socially deprived young women face many barriers and have unequal access to supportive care services after breast cancer ( 78 ). As to the social protection system, persons with a lower SES are more frequently concerned by non-take-up of their social rights, either by lack of information, demand, or attribution ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, literature data on the utilization of these services is rather scarce. The few available studies have reported the existence of numerous barriers, which arise from human, logistic and financial sources, which may restrict access to rehabilitative care for women with BC [21,22].…”
Section: Introductionmentioning
confidence: 99%